Canadian Foreign Direct Investment in the United States: A Discrete Choice Analysis Approach - O'Hagan, Sean (My University, 1998)
Today, nations of the world are economically interdependent of one another. Nowhere is this linkage of domestic economies more evident than between the United States and Canada. Trade and investment between the two countries is the largest in the world. Many Canadians are aware of the importance of the trade that flows between the two countries. Many Canadian are also aware of the huge presence of American multinational enterprises within Canada. However, few appreciate the extent of investment by Canadian firms in the United States.
To understand the importance of Canadian investment in the Untied States, it is essential to understand where Canadian parent companies invest. Or put another way, it is important to know the spatial distribution of Canadian subsidiaries throughout the Untied States. After examining the dispersal of subsidiaries, further questions can follow. The main focus of this thesis is to determine why Canadians invest where they do.
Through the use of a discrete choice analysis it was concluded that Canadian investment in the United States was attracted to the larger American market, accessibility to international inputs and markets, a skilled labor force, and regions with a greater and expanding work force. On the other hand, as unionization, distance, and corporate tax rates increased, the probability of FDI decreased.
FDI in the United States was also separated into large investments and small investments. It was concluded that large investments were attracted to labour with higher skills compared to small investments while poverty and average pay were deemed less important. On the other hand, there was a greater attraction by small investments to states with greater populations and shoreline. As distance increased, small investments experienced a greater decrease when compared to large investments
Keywords: Geography; Geography